Módulo de información computacional que permita seleccionar los sistemas de levantamiento artificial integrando últimas tecnologías para el módulo general de completamiento de Ecopetrol S.A. (2018)
It is presented a module for the selection of artificial lift systems, integrating new technologies for Ecopetrol S.A., in which, with information on certain operating parameters of the well and reservoir previously obtained by the user of the tool, it is possible to give a recommendation on which survey system It would be the most optimal for the production of an oil well integrating as candidates conventional systems and new systems of artificial lift selected according to their applicability in national fields, technological development, balance between advantages and disadvantages and year of publication. As a result, the module delivers a recommendation list in descending order according to the score obtained through the use of the TOPSIS multicriteria decision method.